Analisis Rasio Keuangan Koperasi Syariah : Studi Kasus KSPPS Al-Hikmah - Baginda Sultan Aritonang; Ravika Pebriani; Regita Isna Aisyah; Shella Febrianisa; Ersi sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial ratio analysis is the basis for assessing the performance of the cooperative in managing its financial resources in a given period. Analysis of financial performance KSPPS Al-Hikmah done with regards to the decline in the financial performance of the last few years, whereas KSPPS Al-Hikmah had won the award as the best cooperative of its performance as the city of Bogor. The method used is quantitative method with a descriptive format. The results of these calculation of ratio are then compared with the standard of regulation of Cooperatives and SMEs RI No.06/Per/M.KUKM/V/2006 on Guidelines for Assessment of Cooperative Achievement. The purpose of this study is to determine the financial performance of the KSPPS Al-Hikmah years 2012-2015 in terms of the level of profitability, liquidity and solvency. The results showed that the financial performance KSPPS Al-Hikmah years 2012-2015 seen from the aspect of profitability, liquidity and solvency are generally still below the standard regulation of Cooperatives and SMEs RI No.06/Per/M.KUKM/V/2006. Although in terms of profitability is generally performed quite well, which is between the standard value. KSPPS Al-Hikmah should make corrections to assets in order to make greater contributions in generating SHU, and is expected to increase the capital by attracting more customers cooperatives.